Supramolecular polymer-assisted manipulation of triblock copolymers: understanding the relationships between microphase structures and mechanical properties. Issue 35 (10th May 2021) - Shentu, Zhexian; Zhang, Zhaoming; Zhao, Jun; Chen, Chuanshuang; Wu, Qian; Wang, Lei; Yan, Xuzhou
Abstract : We demonstrate that supramolecular polymers could be utilized to modulate the mechanical properties of triblock copolymers by means of phase-separation engineering. Abstract : Block copolymers with specific microphase-separated structures are a class of important reprocessable elastomers. Numerous approaches have been applied to modify their structures and properties, whereas incorporating supramolecular polymers into the microphase structures has never been achieved. Herein, we report two triblock copolymers in ABA and BAB forms whose hard domains are the A blocks connected by a crown ether-based supramolecular polymer. The ABA triblock copolymer features a regularly distributed hard domain and a tight network, and the rupture of the hard domain is ready to occur upon relatively small deformation. The BAB triblock copolymer shows a hierarchical structure including soft, hard, and secondary hard domains, which results in a relatively tough network. Our work represents a step forward in modifying the phase structures of block copolymers, and would promote the development of block copolymers with emergent properties.